Teaching ESL/EFL listening and speaking - Nation, I. S. P.; Newton, Jonathan (ESL & applied linguistics professional series, 2009)
Using a framework based on principles of teaching and learning, this guide for teachers and teacher trainees offers suggestions for helping learners at various levels of proficiency develop their reading and writing skills and fluency. It features applied principles, useful teaching techniques, and guidelines for testing and monitoring.